054 Characterization of Sleep Phenotypes and Sleep-Dependent Memory Consolidation in a Mouse Model of Fragile X Syndrome. (3rd May 2021) - Martinez, Jessy; Popke, Donald; Donnelly, Marcus; Torres, Daniel; Clawson, Brittany; Jiang, Sha; Aton, Sara
Abstract: Introduction: Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by disruption of Fmr1 gene function, leading to intellectual disability. FXS individuals report increased incidence of sleep disruptions such as loss of NREM sleep, irregular sleep/wake cycles, and circadian rhythm disturbances that warrant pharmacological intervention. Since sleep has critical roles in the promotion of memory consolidation, it is unknown whether disrupted cognitive function in FXS is exacerbated by abnormal sleep. We characterized the link between sleep loss phenotypes and cognition in FXS mice (Fmr1 KO). We hypothesized that normalizing sleep in Fmr1 KO mice could improve sleep-dependent cognitive function. Because direct activation of G-protein inward rectifying potassium (GIRK) channels by ML297 has been found to promote NREM sleep, we tested how ML297 affected sleep and memory consolidation phenotypes in Fmr1 KO mice. Methods: Wild type (WT) and Fmr1 KO were implanted with electrodes for electroencephalogram/electromyogram (EEG/EMG) recording of wakefulness, NREM and REM sleep. Sleep-dependent memory consolidation was measured using single-trial contextual fear conditioning (CFC). ML297 or vehicle was administered after CFC training to measure the effects on sleep and fear memory consolidation. Results: Fmr1 KO mice showed reduced sleep in the hours following CFC learning compared to wild type littermates, and reduced contextual fear memory consolidation. Post-CFC sleep deprivation disrupted memory consolidation in wild type littermates, but not Fmr1 KO mice. Both NREM sleep time and NREM bout length were reduced in Fmr1 KO mice, and preliminary data suggest reduced NREM delta (0.5–4 Hz) power in the prefrontal cortex. These deficits were present at baseline and also following CFC. Post-CFC training administration of ML297 rescued NREM sleep and contextual fear memory deficits in Fmr1 KO mice. Conclusion: Our study showed a strong link between NREM sleep loss and cognitive deficits in Fmr1 KO mice. Critically, normalization of NREM sleep through direct activation of GIRK channels rescues cognitive deficits seen in Fmr1 KO mice, suggesting a new therapeutic approach to treating cognitive deficits associated with FXS. Support (if any): This work was supported by a Rackham Merit Fellowship to JDM.